Ecological risk assessment of pesticides in sediments of Pampean streams, Argentina - Fernández San Juan, M.R. (2023)
After their application in agricultural areas, pesticides are dispersed throughout the environment, causing contamination problems. In Argentina, the main promoter of transgenic biotechnology in the region, the total consumption of agrochemicals has increased significantly in recent years. Most chemicals dumped near surface waters eventually end up in bottom sediments and can be toxic to the organisms that live there. However, published data on the mixing of pesticides in this compartment is still scarce. The objective of this work was to detect and quantify pesticide residues in the sediment of rural streams in the Pampas region and to carry out acute and chronic risk assessment in these aquatic ecosystems. The study area comprises the mountainous system of Tandilia, located in one of the most productive agricultural areas in the country. The concentration of atrazine, acetochlor, chlorpyrifos, cypermethrin, and 2,4-D in the sediment of four rural streams was determined in three different seasons, and the toxic units (TU) and the risk ratios (RQ) were calculated. All the compounds analyzed were detected in most of the sampling seasons and study sites, at concentrations higher than those established in the national and international quality guidelines for the protection of aquatic biota in surface waters and for human consumption. Chlorpyrifos, cypermethrin, and acetochlor were the main pesticides contributing to the TU and RQ values, representing a medium or high ecological risk in most of the sites. Therefore, the evaluation of these pesticides in the bottom sediments could be a decisive factor in assessing the risk to the aquatic environment.